Change in blood pressure status defined by 2017 ACC/AHA hypertension guideline and risk of cardiovascular disease: results of over a decade of follow-up of the Iranian population - Kabootari, Maryam; Tamehri Zadeh, Seyed Saeed; Hasheminia, Mitra; Azizi, Fereidoun; Hadaegh, Farzad (Frontiers in Cardiovascular Medicine, 2023)
Background: Hypertension (HTN) is known as the leading cause of cardiovascular disease (CVD) and mortality. We aimed to assess the impact of 3 years changes in different blood pressure (BP) categories on incident CVD. Methods: In this study, 3685 Tehranian aged ≥ 30 years (42.2% men) free of prevalent CVD with BP level <140/90 mmHg and not on BP-lowering medications were enrolled. Participants were grouped according to baseline BP category using the 2017 ACC/AHA hypertension guideline definition: normal BP (<120/ 80 mmHg), elevated BP (120-129/ < 80), and stage 1 HTN (130-139 and/or 80-89). The hazard ratio (HR) of incident CVD by changes in the BP category was estimated after adjustment for traditional risk factors using Cox’s proportional hazard model, with stable normotension as a reference. Results: During a median follow-up of 11.7 years, 346 CVD events(men=208) occurred. Compare to the reference group, among participants with normal BP at baseline, only those with BP rising to stage 1 HTN (1.47 [(0.99–2.16]) and among those with stage 1 HTN at baseline, regression to elevated BP (1.80 [1.11–2.91]), remaining at stage 1(1.80 [1.29-2.52]), and progression to stage 2 HTN (1.81 [1.25–2.61]) had a higher risk for CVD; moreover, regression to normal BP was associated with 36% increased risk that did not reach to the significant level[(1.36 [0.88-2.12)]. Conversion from elevated BP to any other categories had no significant association with CVD risk. Conclusions: Generally, prevalent stage 1 HTN (regardless of changing category) and incident stage 1 HTN were significantly associated with a higher risk of CVD; even regression to elevated BP, did not attenuate the risk. Accordingly, these populations are potential candidates for anti-hypertensive management. Keywords: Elevated blood pressure, stage 1 hypertension, cardiovascular disease